Arterial hypertension and diabetes mellitus type II in the community El Gramal, Portoviejo - Palma, Andrés S.; Bravo, Diomedes W.; García, Jared F.; Cevallos, Joseph B.; Camejo, Leonardo; Villavicencio, Walter G. (Revista Gregoriana de Ciencias de la Salud, 2025)
Arterial hypertension and type II diabetes mellitus are chronic non-communicable diseases that affect the quality of life of the population of El Gramal. The aim of this study was to analyze the prevalence and risk factors associated with both diseases in a sample of 261 people. The research was conducted between June and August 2023, using a descriptive and cross-sectional approach. The results showed that 72.55% of the participants had arterial hypertension, while 27.45% had type II diabetes mellitus. Factors such as a sedentary lifestyle, a diet rich in carbohydrates, and alcohol consumption significantly influenced the prevalence of these diseases. The study concluded that unhealthy lifestyles are a key factor in the development of hypertension and diabetes in the community, underscoring the need to implement interventions to improve lifestyles and control these chronic conditions.